Implementasi Kepemimpinan Kepala Sekolah dalam Membina Kinerja Guru - Rina Yuliana; Cahya Syaodih; Rita Sulastini (Journal on Education, 2023)
The Covid 19 pandemic which began to spread in Indonesia at the end of 2019 had a major impact on the world of education. With the outbreak pandemic, it has spawned new innovations, namely technology-based learning and internet networks. The essence of the problem formulation in this study is the leadership of the Principal in fostering teacher performance. The problem of improving teacher performance is an unresolved problem in line with the complexity of environmental changes, both in terms of planning, implementation and evaluation. The theological basis in the Al-Qur'an letter Al-Muj is verse 11 and the words of the Prophet Muhammad SAW which means "Indeed, those who act justly, later by Allah's side will be placed on the pulpit of light, are those who are fair in law towards families and whatever handed over (authorized) to them." The main theoretical foundation of this thesis is Leader Shift, John C Maxwell. The research uses a qualitative approach, descriptive method, descriptive study at SDN 1 Grogol and SDN 2 Winong, Cirebon Regency. Data collection techniques in the form of observation, interviews, and documentation on the Principal. Data analysis consists of data reduction, data presentation and drawing conclusions. The results of the study show that the teacher's performance is quite good with the implementation of a good Principal's leadership and is in accordance with the basic concepts described earlier, although there are still a few obstacles in reality. The obstacle that arises is that the teacher's self-actualization process is still not maximal against the programs set by the Principal. The conclusion from this study is that in general, the leadership of a school principal has more or less influenced the performance of teachers, a school principal has many important roles in his efforts to manage and organize the school and all the people involved in it.